Risk mapping of bovine hypodermosis using geographical information system (GIS) in cattle of subtropical region, Pakistan - Khan, Mobushir Riaz; Ahmed, Haroon; Panadero-Fontan, Rosario; Lopez-Sandez, Ceferino; Khan, Muhammad Aamir; Asif, Saira; Mustafa, Irfan; Ali, Muhammad Isthiaq; Raza, Hamid; Qayyum, Mazhar (The Journal of Infection in Developing Countries, 2015)
Introduction: Hypodermosis is an ectoparasitic disease of cattle caused by Hypoderma lineatum and Hypoderma bovis. It is an important health problem of cattle, leading to considerable economic losses. There are various factors that are involved in the spread of this disease such as herd size, location, temperature, humidity, and precipitation. Methodology: Blood samples from 112 herds were collected to determine the presence of Hypoderma spp. infestation. For these herds, size and location were determined; temperature, humidity, and precipitation data were obtained from meteorological stations; and topographic features were obtained from existing maps and through field work. A regression analysis was then used to generate a risk factor analysis profile for hypodermosis and geographic information system (GIS) was used to map the risks. Results: The GIS map developed showed the degree of infestation in different geographical locations at district and village levels. Cluster analysis demonstrated that hypodermosis prevalence varied within zones and across zones. The regression analysis showed that the temperature in the months of January, February, March, August, and November, and the precipitation in September and October had significant results (p < 0.05) when all the risks factors were analyzed. Conclusions: It is concluded that different ecological factors have an important impact on the intensity and infestation rate of hypodermosis across the globe. The present study might be used to control and eradicate the hypodermosis across the globe.